The role of games and pranks as a pedagogical tool in the literacy process of students in the first stage of Elementary School 1 (Research, Society and Development, 2024)
The objective of this study was to analyze the importance of games and balices as a pedagogical tool in the literacy process of students in the first stage of Elementary School I. A literature review was carried out, with a qualitative approach where articles published from 2017 to 2024 were selected. Try to understand how playful and interactive activities can contribute to the learning process, creating a more motivating and engaging environment for students in this age group. Games, by promoting interactivity and fun, facilitate understanding of the content of the school curriculum, as well as students' interest in carrying out diverse activities through playing. The child's literacy process is continuous, carrying out the stages of knowledge. The results revealed that the inclusion of these practices in the school routine not only favored the concepts of sounds and letters, but also contributed to the construction of integral concepts of the child, making learning more active, dynamic and meaningful.